Impact of Standardized Reporting Systems on Patient Experience in Radiology - Igor Toker MD; Sven Jansen PhD; Daniel Lorenz EdiR (Journal of Patient Experience)
Patient experience is a vital measure of healthcare quality, affecting satisfaction, engagement, and outcomes. Standardized radiology reporting can improve care by enhancing communication, reducing errors, and optimizing workflows. This article examines the role of structured reporting and AI in improving patient experience, addressing challenges like workload imbalances and communication issues. Key points include adopting standardized systems, leveraging AI, and focusing on patient-centered communication. Practical tips are shared to boost reporting accuracy, patient engagement, and care quality.